Lenin Reloaded : Toward a Politics of Truth, sic vii - Žižek, Slavoj; Kouvelakis, Eustache, 1965-; Budgen, Sebastian (Book collections on Project MUSE., 2007)
At a time when few people seriously consider alternatives to global capitalism, this work argues that Lenin demonstrates the inseparability of truth and partisanship (the taking of sides), an argument liberal leftists must hear now.